Revealing Ecological Values in Traditional Sasak Bale Tani for Culturally-Rooted Design Innovation - Sigit Wahyudi, Dendi (RUAS, 2025)
The Sasak tribe maintains traditional architectural practices that remain vibrant today, particularly embodied in the Bale Tani structure, which exemplifies local wisdom. Despite the richness of this indigenous knowledge, modern rural development often overlooks its ecological potential, resulting in spatial designs that are culturally disconnected and environmentally unsustainable. This study addresses this gap by examining the ecological principles embedded in the spatial planning of Bale Tani buildings to apply these insights to culturally grounded innovations in sustainable architecture. Employing a qualitative method involving literature review, field observation, and spatial analysis, this research offers a novel contribution by systematically mapping ecological parameters within vernacular Sasak architecture, an area still underrepresented in current architectural discourse. The findings reveal how traditional Sasak layouts promote ecological sustainability, social harmony, and climate-responsive agricultural architecture. These insights underscore the urgency of integrating local architectural wisdom into contemporary rural housing strategies to mitigate environmental degradation and preserve cultural heritage in the face of rapid modernization.